A Simple Transmission Electron Microscopy Method for Fast Thickness Characterization of Suspended Graphene and Graphite Flakes. (25th February 2016) - Rubino, Stefano; Akhtar, Sultan; Leifer, Klaus
Abstract: We present a simple, fast method for thickness characterization of suspended graphene/graphite flakes that is based on transmission electron microscopy (TEM). We derive an analytical expression for the intensity of the transmitted electron beam I 0 ( t ), as a function of the specimen thickness t ( t << λ ; where λ is the absorption constant for graphite). We show that in thin graphite crystals the transmitted intensity is a linear function of t . Furthermore, high-resolution (HR) TEM simulations are performed to obtain λ for a 001 zone axis orientation, in a two-beam case and in a low symmetry orientation. Subsequently, HR (used to determine t ) and bright-field (to measure I 0 (0) and I 0 ( t )) images were acquired to experimentally determine λ . The experimental value measured in low symmetry orientation matches the calculated value (i.e., λ =225±9 nm). The simulations also show that the linear approximation is valid up to a sample thickness of 3–4 nm regardless of the orientation and up to several ten nanometers for a low symmetry orientation. When compared with standard techniques for thickness determination of graphene/graphite, the method we propose has the advantage of being simple and fast, requiring only the acquisition of bright-field images.